(3eLdI cdjI GdJQHjI (B:s (3GdJQHjI hYde GdfaS (B/s - (3LGeYI Yjf TeS(B.s (3cdjI GdJQHjIs ((3GdbGgQI (B:s (3LGeYI Yjf TeS, cdjI GdJQHjIs, 2007)
(3aj GdJQHjI(B.s
(3GdhUa eCNhP ef (B: (3Y(B. 31 (3L(B. 4 (2007)s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdJQHjIs -- (3OhQjGJs